Voltaire and the English - Besterman, T (Voltaire Foundation, 2017)
Transactions of the Oxford Colloquium held at the Taylor Institution from 26 to 28 May 1978 R. Pomeau, Les Lettres philosophiques: le projet de Voltaire A.-M. Rousseau, Naissance d'un livre et d'un texte: les Letters concerning the English nation W. H. Barber, Voltaire and Samuel Clarke P. Casini, Briarée en miniature: Voltaire et Newton D. Williams, Voltaire's war with England: the appeal to Europe 1760-1764 S. S. B. Taylor, Voltaire's humour J. Scherer, 'L'univers en raccourci': quelques ambitions du roman voltairien J. Vercruysse, Voltaire, Sisyphe en Jermanie: vers la meilleurs des éditions possibles Catalogue of an exhibition of books and manuscripts shown in the Divinity School, Bodleian Library from 2 to 27 May 1978 G. Barber, Voltaire and the English: catalogue of an exhibition W. H. Barber, Voltaire et Newton Norma Perry, The Rainbow, the White Peruke and the Bedford Head: Voltaire's London haunts W. H. Barber, Theodore Besterman